Eski türkçeden günümüze türkçede kelimesi - ERSOY, Feyzi (Acta Mongolica, 2005)
In this article, the word “ba§” (head), one of the organs of a human body was examined. After dwelling upon how the word “ba§” is used in Turkey Turkish, it was tried to show how the same word was used in the historical artifacts and textbooks of the periods of Orkhon, Uighur and Karahans. It was seen that the word “ba§” was used in the Turkey Turkish dictionaries and in the idioms many times with its basic and subsidiary meanings. On the other hand, when we look at the period of old Turkish language, we observe that the word was most widely used in Kutadgu Bilig.